2012
DOI: 10.1007/s00276-012-0984-1
|View full text |Cite
|
Sign up to set email alerts
|

An anatomic study of structure and innervation of the serratus anterior muscle

Abstract: This study demonstrated that the innervation of the serratus anterior muscle was different in each part. The difference indicates that the superior part has an intimate relation with the levator scapulae muscle while the middle and inferior parts could be the actual serratus anterior muscle. Moreover, the distribution of branches from the intercostal nerves shows that the inferior part has a connection with some trunk elements. Understanding these characteristics of innervation is useful to identify the cause … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…This innervation pattern and the observation that the serratus anterior muscle may blend with the levator scapulae muscle (albeit rarely) have led some to suggest that the superior portion of the serratus anterior muscle may be considered as developing from the rhomboid sheet. Nasu et al (2012) also found that the lower portion of the serratus anterior muscle, as well as being supplied by the long thoracic nerve can also receive input from branches of intercostal nerves. Nasu et al (2012) also found that the lower portion of the serratus anterior muscle, as well as being supplied by the long thoracic nerve can also receive input from branches of intercostal nerves.…”
Section: Serratus Anteriormentioning
confidence: 86%
“…This innervation pattern and the observation that the serratus anterior muscle may blend with the levator scapulae muscle (albeit rarely) have led some to suggest that the superior portion of the serratus anterior muscle may be considered as developing from the rhomboid sheet. Nasu et al (2012) also found that the lower portion of the serratus anterior muscle, as well as being supplied by the long thoracic nerve can also receive input from branches of intercostal nerves. Nasu et al (2012) also found that the lower portion of the serratus anterior muscle, as well as being supplied by the long thoracic nerve can also receive input from branches of intercostal nerves.…”
Section: Serratus Anteriormentioning
confidence: 86%
“…Below the eighth thoracic level the lower 4 slips of the serratus anterior muscle interdigitate at their origins with the upper 5 slips of the external oblique muscle. 25 Also below the eighth thoracic level, the serratus anterior muscle ends and this tissue plane becomes deep to the latissmus dorsi and the upper part of the external oblique muscle.…”
Section: Results Of the Cadaveric Studymentioning
confidence: 99%
“…The serratus anterior originates on the surface of the 1 st to 10 th ribs at the side of the chest and inserts along the whole anterior length of the medial border of the scapula. This muscle is innervated by branches of sympathetic roots C5-C7 [78] (see Figure 20). The muscle set lifts the ribs when the shoulder girdle is fixed, and is is a set of inspiratory muscle.…”
Section: Four Inspiratory Muscles Attached To the Ribs And Scapulamentioning
confidence: 99%
“…The main expiratory muscles considered here (with more information Figure 20. According to the findings of [78], branches of spinal roots C5, C6, C7 innervate the inspiratory serratus anterior muscles in humans. Refer also to Table A9.…”
Section: Expiratory Muscles-with the Superior Part Of The Largest Musmentioning
confidence: 99%